Diagnosis of visceral leishmaniasis in Bihar India: comparison of the rK39 rapid diagnostic test on whole blood versus serum. - Greg Matlashewski; Vidya Nand Ravi Das; Krishna Pandey; Dharmendra Singh; Sushmita Das; Ayan Kumar Ghosh; Ravindra Nath Pandey; Pradeep Das (Public Library of Science (PLoS), 2013)
BACKGROUND: Antibody-detecting rapid diagnostic tests (RDTs) against rK39 are available to aid in the diagnosis of visceral leishmaniasis (VL). Although these rK39 RDTs have been developed, validated and approved for use with serum, they are universally performed using whole blood. It was therefore necessary to determine whether this RDT is as sensitive on whole blood as on serum. METHOD AND PRINCIPAL FINDINGS: In this study we compared the rK39 RDT on serum and blood samples from 624 individuals with symptoms of VL attending the outpatient clinic at the Rajendra Memorial Research Institute of Medical Sciences, Patna, India. A total of 251 cases (40%) were both serum and blood-positive and 26 cases (4%) were identified as blood-negative and serum-positive. These 26 individuals in general had low titer antibodies against rK39 as determined by ELISA and follow-up on most of these individuals revealed none had persistent VL symptoms. The Cohen kappa index comparing blood and serum was 0.88 indicating excellent concordance. CONCLUSION: Although the concordance was excellent, it is possible to miss rK39 positive individuals when using blood and the titer of anti-rK39 antibodies is low. We recommend that when an individual from an endemic area has obvious clinical symptoms of VL and the whole blood rK39 RDT is negative, that the test should be redone 2-3 weeks later if the symptoms persist.